The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1007/s007010050324
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation for Medically Refractory Epilepsy; Efficacy and Cost-Benefit Analysis

Abstract: VNS is an effective treatment of refractory epilepsy and remains effective during long-term follow-up. Cost-benefit analysis suggests that the cost of VNS is saved within two years following implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 3 publications
1
34
2
Order By: Relevance
“…Approximately 25%-30% of patients who are deemed surgical candidates at our center undergo VNS instead of intracranial epilepsy surgery. We agree with authors from other centers 12,41 and stress that VNS-despite its apparent simplicity and safety-should be considered as a palliative treatment option for children with treatment-resistant epilepsy but only after thorough evaluation to exclude those children who may benefit from intracranial surgery.…”
Section: Study Limitationssupporting
confidence: 70%
See 1 more Smart Citation
“…Approximately 25%-30% of patients who are deemed surgical candidates at our center undergo VNS instead of intracranial epilepsy surgery. We agree with authors from other centers 12,41 and stress that VNS-despite its apparent simplicity and safety-should be considered as a palliative treatment option for children with treatment-resistant epilepsy but only after thorough evaluation to exclude those children who may benefit from intracranial surgery.…”
Section: Study Limitationssupporting
confidence: 70%
“…6,11,12,32 Authors reported significant decreases in hospital admissions, length of stay, intensive care unit admissions, and emergency room visits and estimated that the cost of the device and implantation (roughly $10,000) can be recovered within 2-3 years after initiation of VNS therapy. 6,11,12,32 Given the long life expectancy of children, these results may translate into a significant cost savings over time.…”
Section: Efficacy Of Vnsmentioning
confidence: 99%
“…42 VNS may also decrease the annual number of hospital admissions required per year, as well as epilepsy-related direct medical costs. 43 These open-label pilot studies led to the onset of multicenter, double-blind, randomized control trials for VNS in medically refractory epilepsy. 8,16,44,45 Results from these trials revealed a mean or median seizure frequency reduction of 24 -31% over 3 months of follow-up in patients receiving the high VNS treatment paradigm (i.e., VNS at therapeutic stimulatory parameters, such as 30 Hz, 30 s on, 5 min off, 500-ks pulse width).…”
mentioning
confidence: 99%
“…The cost of VNS was saved within 2 years following implantation of the device in drug resistant epilepsy (Boon et al, 1999). In the same way, the treatment of IBD is estimated to be reduced with VNS.…”
Section: Questions-future For Vagus Nerve Stimulation In Inflammatorymentioning
confidence: 99%